JAYAPURA CITY KUA STRATEGY IN IMPLEMENTING PMA. No. 34 of 2016. Concerning Duties and Functions - Amri - Amri; Dyah Margo Mukti (Universitas Islam Negeri Ar-Raniry, 2022)
Minister of Religion Regulation Number 34 of 2016 concerning the organization and governance of the Sub-District KUA, it is seen that the duties and functions of the Jayapura City KUA must be as much as possible to implement these regulations. Therefore, this study aims to see what obstacles are faced and what strategies are carried out by the Jayapura City KUA in implementing the Perma. This research is a qualitative research that is through interviews, observations and documentation that has been processed and analyzed. The results of the study show the obstacles faced in implementing Perma No. 34 of 2016 is the limitation of existing Human Resources (Employees) and Collaboration with work partners has not been going well. Then the strategy taken in implementing the regulation is the first, increasing the number of employees within the Ministry of Religion of Jayapura City through the acceptance of Civil Servants every year since 2019. Second, coordinating and collaborating with Islamic religious instructors in Jayapura City to be able to help maximize the duties and functions of KUA in the field of outreach to the community.